Effect of Oxygen Depletion to the Cathode on the Working of Solid Oxide Fuel Cells. (30th May 2017) - Thambiraj, Nelson; Suciu, Crina; Waernhus, Ivar; Vik, Arild; Hoffmann, Alex C.
Abstract : The performance of solid oxide fuel cells operating with varying oxygen concentrations, decreasing from an initial concentration of 21% (air), in the gas supplied to the cathode is investigated systematically operating the cells at three different temperatures, namely 800, 850 and 900C.The performance is characterized by determining the I-V curves ofthe cells, whereby it is possible to roughly distinguish between ohmic polarization and concentration polarization. The most dramatic effects of decreasing the oxygen partial pressure to the cathode was found at oxygen concentrations below 12.6%, where the onset of concentration polarization limitation was seen to start to dominate at the highest power densities. After testing it was found that the cells recovered their performance almost completely, when again supplied with air to the cathode, except in one case (the cell tested at 850C) where a threshold low oxygen concentration appears to have been reached during the testing causing the cell to recover less completely.